Association between HLA class I and class II alleles and the outcome of West Nile virus infection: an exploratory study. - Marion C Lanteri; Zhanna Kaidarova; Trevor Peterson; Steven Cate; Brian Custer; Shiquan Wu; Maria Agapova; Jacqueline P Law; Thomas Bielawny; Frank Plummer; Leslie H Tobler; Mark Loeb; et al. (PLoS ONE, 2011)
West Nile virus (WNV) infection is asymptomatic in most individuals, with a minority developing symptoms ranging from WNV fever to serious neuroinvasive disease. This study investigated the impact of host HLA on the outcome of WNV disease.A cohort of 210 non-Hispanic mostly white WNV(+) subjects from Canada and the U.S. were typed for HLA-A, B, C, DP, DQ, and DR. The study subjects were divided into three WNV infection outcome groups: asymptomatic (AS), symptomatic (S), and neuroinvasive disease (ND). Allele frequency distribution was compared pair-wise between the AS, S, and ND groups using χ2 and Fisher's exact tests and P values were corrected for multiple comparisons (Pc). Allele frequencies were compared between the groups and the North American population (NA) used as a control group. Logistic regression analysis was used to evaluate the potential synergistic effect of age and HLA allele phenotype on disease outcome.The alleles HLA-A*68, C*08 and DQB*05 were more frequently associated with severe outcomes (ND vs. AS, P(A*68) = 0.013/Pc = 0.26, P(C*08) = 0.0075/Pc = 0.064, and P(DQB1*05) = 0.029/Pc = 0.68), However the apparent DQB1*05 association was driven by age. The alleles HLA-B*40 and C*03 were more frequently associated with asymptomatic outcome (AS vs. S, P(B*40) = 0.021/Pc = 0.58 and AS vs. ND P(C*03) = 0.039/Pc = 0.64) and their frequencies were lower within WNV(+) subjects with neuroinvasive disease than within the North American population (NA vs. S, P(B*40) = 0.029 and NA vs. ND, P(C*03) = 0.032).Host HLA may be associated with the outcome of WNV disease; HLA-A*68 and C*08 might function as "susceptible" alleles, whereas HLA-B*40 and C*03 might function as "protective" alleles.